Pengaruh Faktor Fisik Tanah Terhadap Penurunan Produksi Jagung Dan Implikasinya Terhadap Pendapatan Petani Di Marelan - Ryan Pramana; Putri Roito; Vinny Natasya; Sara Anjelina (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research explores the factors that influence the income of corn farmers in Marelan, as well as analyzing the impact of these factors and formulating strategies for increasing income. Corn is an annual plant with a life cycle of 80 to 150 days, and is important as a source of carbohydrates. This research uses a qualitative descriptive method with data analysis from various sources such as magazines, Google and trusted websites. The research results show that land area, capital, crop yields and number of workers have a significant influence on corn farmers' income. Recommended strategies include the use of modern agricultural technology, training and education of farmers, as well as collaboration with research institutions, government and private organizations. Increasing farmer income can be achieved through optimizing production resources and effective management. In conclusion, production factors such as land, capital and labor greatly influence corn farmers' income, and strategic steps need to be taken to ensure sustainability and increase farmer income.